Bronchial artery embolization as a life-saving method in a case of massive hemoptysis secondary to a hemorrhagic bullous emphysema - Youssef Bouktib; Ayoub El Hajjami; Badr Boutakioute; Merieme Ouali Idrissi; Najat Cherifi Idrissi El Ganouni (Radiology Case Reports)
Bullous emphysema, often associated with COPD, can lead to severe complications like massive hemoptysis. The Bronchial artery embolization (BAE) has become a well-established and effective procedure for the management of hemoptysis, which is the expectoration of blood from the lower respiratory tract. First introduced in the 1970s, BAE has evolved significantly due to advancements in interventional radiology techniques and embolic materials. The success rate of BAE in controlling acute hemoptysis ranges from 70% to 90% in the literature. However, recurrence rates remain a challenge, with studies reporting recurrence in up to 20%-30% of cases within the first year, often due to incomplete embolization or disease progression. Repeat embolization is frequently required in these patients, highlighting the importance of close follow-up and management of the underlying disease.This case report describes a 55-year-old patient with a history of pulmonary tuberculosis, chronic smoking, and advanced COPD who presented with significant hemoptysis due to a hemorrhagic emphysematous bulla. Due to the patient's fragile condition, surgical intervention was deemed too risky, and embolization was chosen as a less invasive alternative. The procedure successfully controlled the bleeding without complications. This case highlights the importance of bronchial artery embolization (BAE) as a life-saving intervention in cases of massive hemoptysis, particularly in patients unfit for surgery. While BAE provides an effective solution for acute bleeding, long-term management of COPD and close follow-up are essential to prevent recurrence. A multidisciplinary approach is crucial for optimal patient outcomes.